Prarancangan Pabrik Dimetil Formamid dari Metil Formiat dan Dimetil Amin Kapasitas 75000 Ton/Tahun - , LARS STARNER REGEN; , Prof.Ir.Arief Budiman,M.S.,D.Eng ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Dimethylformamide manufacturing process takes place in the flow stirred tank reactor. The reaction takes place in the gas phase with a temperature of 60ÂºC and a pressure of 5 atm. Due to the exothermic reaction of running, water used as a coolant. The need for water utilities include as much 55.056 m3 / hour derived from the river around Karawang,, steam as much as 7695.0 Kg / h generated by the boiler. The utilities also needs 7211 Litre of fuel oil / hour and 11676,9 kg/hour of compressed air . Dimetilformamide plant with a capacity of 75,000 tonnes / year will be established in Karawang, West Java, with a land area of 30 hectares and 200 employees. Fixed capital investment of $ 13,142,270.86 + Rp 69,182,944,000 , workingcapital of $ 576.277.44 + Rp 316 172 757 000 , ROI before taxes 39.97 % , and 23.98 % ROI after tax while the POT is a 2,001 -year pre-tax and after tax 2,943 years . Break even point 48.90 % , 32.20 % shut down point . In terms of the economy and the need for the establishment of Dimetilformamid factory in Indonesia , the plant with a capacity of 75,000 tonnes per year is quite exciting to be reexamined to set up in Indonesia .